Asymmetric Synthesis of Functionalized Dihydro- and Tetrahydropyrans via an Organocatalytic Domino Michael–Hemiacetalization Reaction - Urbanietz, Gregor; Atodiresei, Iuliana; Enders, Dieter (Synthesis, 2014)
Starting from α-hydroxymethyl nitroalkenes and various 1,3-dicarbonyl compounds, a one-pot organocatalyzed diastereo- and enantioselective synthesis of polyfunctionalized dihydro- and tetrahydropyran derivatives via a domino Michael-hemiacetalization sequence is reported. The title compounds bearing a variety of functional groups can be synthesized in this way in good yields (59–91%) and with moderate to excellent diastereoselectivities (26–98% de) and enantioselectivities (71–99% ee).
Keywords: organocatalysis; domino reaction; one-pot reaction; tetrahydropyrans; hydrogen bonding